Cursed moon - Wells, Jaye (Wells, Jaye. Prospero's war., 2014)
When a rare Blue Moon upsets the magical balance in the city, Detective Kate Prospero and her Magic Enforcement colleagues pitch in to help Babylon PD keep the peace. Between potions going haywire and emotions running high, every cop in the city is on edge. But the moon's impact is especially strong for Kate, who's wrestling with guilt over her use of illegal magic. When a rogue wizard steals dangerous potions from a local coven, Kate's team must find the thief's hideout before the vengeful coven catches him. But the investigation uncovers the rogue's dangerous plot to unleash chaotic magic on the city. Once the Blue Moon rises no-one's secrets will be safe. Not even Kate's.